Antidiabetic Effect of Ethanol Extracts of Chia Seed and Tiger Nut and Their Combination on Body Weight and Fasting Blood Glucose in Alloxan-Induced Diabetic Rats - Chinyere S. Nwaka; Andrew C. Nwaka; Jonathan C. Ifemeje (Health Science Research International, 2026)
Diabetes mellitus is a chronic metabolic disorder marked by hyperglycaemia and progressive weight loss, and there is growing interest in plant-derived functional foods as low-cost adjuncts to conventional therapy. This study evaluated the effect of ethanol extracts of chia seed (Salvia hispanica), tiger nut (Cyperus esculentus), and their combination on body weight and fasting blood glucose (FBG) in alloxan-induced diabetic Wistar rats. Sixty-three male rats were assigned to nine groups of seven: normal control (A), diabetic untreated (B), diabetic + 100 mg/kg metformin (C), diabetic + 150 or 300 mg/kg chia extract (D, E), diabetic + 150 or 300 mg/kg tiger nut extract (F, G), and diabetic + 150 or 300 mg/kg combined extract (H, I). Diabetes was induced by a single intraperitoneal injection of 160 mg/kg alloxan monohydrate, and animals with FBG above 250 mg/dl were used. Extracts were administered orally once daily for 21 days; body weight was recorded weekly and FBG at three-day intervals. Diabetes induction produced marked weight loss and hyperglycaemia in all diabetic groups relative to the normal control. From the first week of treatment, all extract-treated groups showed a progressive gain in body weight alongside a progressive decline in FBG, with the pattern most pronounced in the groups receiving 300 mg/kg of the combined chia seed and tiger nut extract. By day 21, FBG in the high-dose combination group had fallen furthest among the extract-treated groups, approaching the trend seen with metformin. These findings suggest that ethanol extracts of chia seed and tiger nut, and particularly their combination, help restore body weight and glycaemic control in alloxan-induced diabetic rats, supporting their potential as adjunct antidiabetic agents.